Factors influencing perceptions on wasiyyah among Malaysian Muslims community / Nur Fathiah Farzana Roslan - Roslan, Nur Fathiah Farzana (2019)
Estate planning can be defined as the process of analysing and making decision on how the personal asset will be managed and distributed to others in the event of person death or disability. The objective of making estate planning is to ease the process of managing and distributing the inheritance to theirs heirs. In Malaysia, the problem on the number of unclaimed inheritance and frozen asset increase from year to year. Wasiyah is another way that Muslims can performed to distribute the wealth during their lifetime to their heirs. It will be result a better planning in distribution of estate after the death of the person. The purpose of this study is to investigate the factors that influence perceptions on wasiyyah among Malaysian Muslims community. The dependant variable in this study is the perception on wasiyyah among Malaysian Muslims community. Knowledge, financial obligation, organization and religiosity are being used as independent variables. The data had been collected by distribution of questionnaires through Google Forms and hand by hand method to the 205 respondent in Sungai Petani area. The data is classified as primary data and had been analysed using the Statistical Package for Social Science (SPSS). The SPSS had been produced the result of frequency analysis, descriptive analysis, factor analysis, correlation analysis and regression analysis. Our results shows that knowledge and financial obligation significantly related with perceptions on wasiyyah among Malaysian Muslims community in Sungai Petani area.